Combustion performance of a low NOx gas turbine combustor using urea addition into liquid fuel. (15th March 2021) - Fontanarosa, Donato; De Giorgi, Maria Grazia; Ciccarella, Giuseppe; Pescini, Elisa; Ficarella, Antonio
Highlights: Water in Jet-A1 fuels with urea contamination in lean-burning combustor was studied. Pollutant and temperature measurements coupled with high-speed visualizations. The POD of the OH* chemiluminescence acquisitions characterized the flame stability. NOx reduced by the leaning of the flame with significant combustion losses. Same NOx drop, stable flame, no efficiency loss with 2.5 wt%water-2 wt%urea content. Abstract: The present work provides an experimental investigation on the effects of the urea addition in water emulsified fuels in terms of combustion performance and emissions. Experiments have been carried out using a test rig equipped with a 300-kW Jet-A1 fueled swirling burner operating under lean conditions. Different equivalence ratios and various urea in water percent concentrations have been tested. Measurements of temperature and emissions have been performed, in combination with high-speed flame imaging in visible and ultraviolet spectral ranges. Results have shown that the use of 2.5 wt% (percent concentration by weight) water-2 wt% urea solution into Jet-A1 fuel represents a promising combustion control strategy, since it leads to the same nitrogen oxides (NOx ) reduction of a leaner neat fuel flame (about 30% less than the neat fuel case), but without significant penalty on the overall combustion performance, viz. combustion temperature, thermal and combustion efficiencies and pollutant emissions. The snapshot Proper Orthogonal Decomposition (POD) of the broadband flame emission images, methylidyne radical and hydroxyl radical chemiluminescence allowed to characterize of the flame dynamics and the flame stability. Differences between the flame regimes were also investigated by the POD mode 3 eigenstructure. The reduced flame stability for the leaner operating condition was confirmed by the energy increase of the first POD modes. The more unstable flame dynamics was confirmed by the frequency distribution of the phase points in the POD phase-space of modes 1 and 2 that highlighted a significant rise of the phase angles occurrence in the range [−π/6, π/6].